ADVANCED FOREIGN EXPERIENCES IN COST ACCOUNTING AND COST CALCULATION (American Journal of Business Management, Economics and Banking, 2024)
In the article, advanced foreign experiences in the field of cost accounting and cost calculation and their integration into the network of business entities operating in Uzbekistan, analysis and accounting of production costs, product (works, services) costs the main types of modern methods are considered. Here, the concepts and traditional approaches of product costing popular in domestic and foreign countries and common methods in foreign practice are described.